Q: C plus 5 over -3 equals 18?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

2+14=16

It's hard to tell what formula you mean from your description, but I think you mean 4 times 3 divided by 4 plus 10 times 5 over 12. Normally multiplication and division is performed before addition so this equals (4 * 3 / 4) + (10 * 5 / 12) 4 times 3 divided by 4 equals 12 divided by 4 equals 3 and on the other side of the plus 10 times 5 divided by 12 equals 50 divided by 12 50 doesn't go exactly into 12 but we can make it equal 25 over 6 to add the results we need to evaluate 3 plus (25 over 6) to do this, we have to use a lowest common denominator, in this case 6 3 plus (25 over 6) equals 3 * 6 over 6 plus (25 over 6) equals (18 over 6) plus (25 over 6) equals (18 + 25) over 6 43 over 6 43 over 6 is a vulgar fraction, so we extract as many whole numbers as possible 43 over 6 equals 42 over 6 plus 1 over 6 equals: 7 plus 1 over 6 7 1/6

The answer is 21 because if 21 is divided by 3 it equals 7 plus 4 equals 11.

3 + 3 = 6 6 x 3 = 18 18 - 3 = 15 15 + 3 = 18

2 over 3 plus 5 over 9 equals 11 over 9 or 1 and 2 ninths.

Related questions

An equation where X = 18

It is an equation and the value of y is 18

No.

2+14=16

No. -18 / 3 = -6

18 - 9 - 3 + 5 = 1

18 because you add three then subtract three

It's hard to tell what formula you mean from your description, but I think you mean 4 times 3 divided by 4 plus 10 times 5 over 12. Normally multiplication and division is performed before addition so this equals (4 * 3 / 4) + (10 * 5 / 12) 4 times 3 divided by 4 equals 12 divided by 4 equals 3 and on the other side of the plus 10 times 5 divided by 12 equals 50 divided by 12 50 doesn't go exactly into 12 but we can make it equal 25 over 6 to add the results we need to evaluate 3 plus (25 over 6) to do this, we have to use a lowest common denominator, in this case 6 3 plus (25 over 6) equals 3 * 6 over 6 plus (25 over 6) equals (18 over 6) plus (25 over 6) equals (18 + 25) over 6 43 over 6 43 over 6 is a vulgar fraction, so we extract as many whole numbers as possible 43 over 6 equals 42 over 6 plus 1 over 6 equals: 7 plus 1 over 6 7 1/6

2 over 3 = 18 over x+5... x=22 because (x+5) needs to equal 27 for the equation to be true.

1 over 3 plus 1 over 12 equals 5 over 12

5x+18 = 2x+9 5x-2x = 9-18 3x = -9 x = -3 and y = 3

you mean: x+3x+3=x+18 so x=5